Status of Citrus tristeza virus (CTV) in Peninsular Malaysia - Ayazpour, Kavous; Sijam, Kamaruzaman; Vadamalai, Ganesan; Jaafar, Hawa Z. E. (Academic Journals, 2011)
Citrus tristeza virus (CTV) is the most important viral disease of Citrus spp. and has a worldwide distribution. Results of ELISA and PCR showed that all Citrus varieties includingFortunella sp., Citrofortunella microcarpa and Citromelo in major citrus growing areas of Malaysia had a high infection rate with CTV. In most areas, pomelo however was free of infection, but in Cameron Highlands, we found some strains of CTV that were severe to Citromelo and pomelo. Phylogeny studies revealed that these strains were similar to CTV isolates from China and Japan and were very different from CTV isolates from USA and New Zealand.